2021
DOI: 10.21203/rs.3.rs-41389/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deficient macrophage autophagy protects mice from Cerium Oxide nanoparticle-induced lung fibrosis

Abstract: Background: Cerium (Ce) is a rare earth element, rapidly oxidizing to form CeO2, and currently used in numerous commercial applications, especially as nanoparticles (NP). The potential health effects of Ce remain uncertain, but literature indicates the development of rare earth pneumoconiosis accompanied with granuloma formation, interstitial fibrosis and inflammation. The exact underlying mechanisms are not yet completely understood, and we propose that autophagy could be an interesting target to study, parti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…It maintains the homeostasis of the intracellular environment by forming autophagosome vesicles, engulfing dysfunctional cytoplasm and organelles, and forming autolysosomes to degrade the contents of vesicles (89,90). Autophagy disorder involves various diseases, also including IPF (91)(92)(93)(94)(95)(96). Accumulating evidence revealed that autophagy activity was impaired in IPF, and inhibition of autophagy could induce myofibroblast proliferation and ECM deposition, thus leading to fibrosis (97,98).…”
Section: Autophagymentioning
confidence: 99%
“…It maintains the homeostasis of the intracellular environment by forming autophagosome vesicles, engulfing dysfunctional cytoplasm and organelles, and forming autolysosomes to degrade the contents of vesicles (89,90). Autophagy disorder involves various diseases, also including IPF (91)(92)(93)(94)(95)(96). Accumulating evidence revealed that autophagy activity was impaired in IPF, and inhibition of autophagy could induce myofibroblast proliferation and ECM deposition, thus leading to fibrosis (97,98).…”
Section: Autophagymentioning
confidence: 99%